THE STRUCTURE AND MEANING OF KAWIH IN RONGGENG GUNUNG PERFORMANCE - Dian Nurrachman; Hasbi Assiddiqi; Rohanda Rohanda; Deden Hidayat (PARADIGM: Journal of Language and Literary Studies, 2019)
Ronggeng Gunung is a combined performing art which thrives especially in southern Ciamis (including Pamarican and Banjarsari) and Pangandaran (including Padaherang and Kalipucang). Generally, this is almost the same as the conventional ronggeng, in which a dancer performs while being accompanied by gamelan (Javanese/Sundanese music instrument) and kawih (Sundanese songs). The main ronggeng dancer is a woman who wears a shawl as a part of the dance to invite males to dance with her. Allegedly, in its mythological narratives, Ronggeng Gunung was created from the grief of a princess who lost her beloved husband and her attempt of revenge toward the killer. This paper is actually intended to find out how are the structures and meanings of Kawih as an inseparable part of Ronggeng Gunung performance. This study applies structuralism as both theoretical approach and method, since it provides the theoretical framework to find out both the structural construction and the meaning of the Kawih. The result of this study shows that kawih accompanying Ronggeng Gunung performance represents a passionate romance of solace, unrequited love, as well as the cultural values of modesty, politeness, and the importance of solidarity in facing every problem encountered by human.